The Three Colorado Rivers: Hydrologic, Infrastructural, and Economic Flows of Water in a Shared River Basin. (21st February 2022) - Rushforth, Richard R.; Zegre, Nicolas P.; Ruddell, Benjamin L.
Abstract: The Colorado River Basin is a hydrologic river network that directs runoff from rain and snow falling on mountains, primarily in Colorado and Wyoming, to the Colorado River Delta in Mexico. Over the last century, in response to basin‐wide water shortages, legal agreements between stakeholders in seven U.S. states and Mexico, hydrologic flows from users on the main stem of the river have been reallocated to junior water rights holders. Municipalities, businesses, farmers, and households utilize the Colorado River water to produce and trade valuable, water‐derived goods and services, which effectively reallocates water through a continually adapting, boundary‐free economic river network providing indirect access to "virtual" Colorado River water. We conceptualize the Colorado River Basin as a multiplex network comprised of interdependent natural flow networks, direct (infrastructural) flow networks, and indirect (virtual) flow networks. Using this reframing, we quantify the total hydrosocial impact of the Drought Contingency Plan (DCP) on Lower Basin states. For each Mm 3 of water reduced through the DCP, Arizona, Nevada, and California lose an additional 0.42–0.43 Mm 3, 0.33–0.51 Mm 3, and 1.06–1.10 Mm 3 of virtual water flow, respectively. Hence, the DCP will require Arizona, Nevada, and Southern California to restructure how they use water, relying less on direct and indirect consumption of the Colorado River water and finding more indirect water sources outside that basin.